The judicial system in the territory of Belarus in 1797–1840 - Hushchynski, Ihar H. (Journal of the Belarusian State University. History, 2020)
The article presents the study of the judicial system that operated on the territory of Belarus from 1797–1840, i. e., from the time of Paul I reforms to the abolition of local features in the sphere of justice by Nikolai I and the introduction of the Russian model of judicial system and legal proceedings. At this time, the judicial system of the region was significantly different from that in the inner provinces of the empire. In this judicial system, retaining of the local judicial legal tradition of the times of the Grand Duchy of Lithuania and the Polish-Lithuanian Commonwealth was combined with the use of Russian law. This judicial system has been operating, albeit with some changes, for more than 3 decades, while under the influence of the anti-Russian uprising of 1830–1831 the autocracy did not proceed to eliminate local features in the judicial sphere. This judicial system has operated, albeit with some changes, for more than 3 decades – until when under the influence of the uprising of 1830–1831 the autocracy proceed to eliminate local features in the judicial sphere.